Unraveling the time-dependent relevance of input model uncertainties for a lumped hydrologic model of a pre-alpine karst system 论阿尔卑斯前缘岩溶系统集总水文模型输入模型不确定性的时间相关性 Comprendre l’importance temporelle des incertitudes des modèles d’entrée pour un modèle hydrologique global d’un système karstique préalpin Desfazendo a relevância temporal das incertezas do modelo de entrada para um modelo hidrológico de um sistema de cárstico pré-alpino Análisis de la relevancia temporal de las incertidumbres en los modelos de entrada para un modelo hidrológico compuesto en un sistema kárstico prealpino - Bittner, Daniel; Richieri, Beatrice; Chiogna, Gabriele (Hydrogeology Journal, 2021)
Uncertainties in hydrologic model outputs can arise for many reasons such as structural, parametric and input uncertainty. Identification of the sources of uncertainties and the quantification of their impacts on model results are important to appropriately reproduce hydrodynamic processes in karst aquifers and to support decision-making. The present study investigates the time-dependent relevance of model input uncertainties, defined as the conceptual uncertainties affecting the representation and parameterization of processes relevant for groundwater recharge, i.e. interception, evapotranspiration and snow dynamic, on the lumped karst model LuKARS. A total of nine different models are applied, three to compute interception (DVWK, Gash and Liu), three to compute evapotranspiration (Thornthwaite, Hamon and Oudin) and three to compute snow processes (Martinec, Girons Lopez and Magnusson). All the input model combinations are tested for the case study of the Kerschbaum spring in Austria. The model parameters are kept constant for all combinations. While parametric uncertainties computed for the same model in previous studies do not show pronounced temporal variations, the results of the present work show that input uncertainties are seasonally varying. Moreover, the input uncertainties of evapotranspiration and snowmelt are higher than the interception uncertainties. The results show that the importance of a specific process for groundwater recharge can be estimated from the respective input uncertainties. These findings have practical implications as they can guide researchers to obtain relevant field data to improve the representation of different processes in lumped parameter models and to support model calibration.
CRIS-Team Scopus Importer:2024-04-17
Keywords: Conceptual models; Groundwater recharge; Input uncertainties; Karst; Rainfall-runoff